2021
DOI: 10.1111/imcb.12450
|View full text |Cite
|
Sign up to set email alerts
|

State‐of‐the‐art microscopy to understand islets of Langerhans: what to expect next?

Abstract: The discovery of Langerhans and microscopic description of islets in the pancreas were crucial steps in the discovery of insulin. Over the past 150 years, many discoveries in islet biology and type 1 diabetes have been made using powerful microscopic techniques. In the past decade, combination of new probes, animal and tissue models, application of new biosensors and automation of light and electron microscopic methods and other (sub)cellular imaging modalities have proven their potential in understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…In the human islets of Langerhans, different endocrine cell types were distinguished according to their secretory granule morphology under transmission electron microscope. In line with what was previously found, 25 , 26 glucagon granules of alpha were dark with a thin halo, insulin granules of beta were lighter gray with a thick halo, mature granules had a crystalline core, and somatostatin granules of delta were homogeneously light gray without any halo ( Figure 3 E). Immunogold electron microscopic investigation revealed that gold particles labeling GLRA1 were mainly localized in the haloes of insulin granules of beta ( Figure 3 F).…”
Section: Resultssupporting
confidence: 91%
“…In the human islets of Langerhans, different endocrine cell types were distinguished according to their secretory granule morphology under transmission electron microscope. In line with what was previously found, 25 , 26 glucagon granules of alpha were dark with a thin halo, insulin granules of beta were lighter gray with a thick halo, mature granules had a crystalline core, and somatostatin granules of delta were homogeneously light gray without any halo ( Figure 3 E). Immunogold electron microscopic investigation revealed that gold particles labeling GLRA1 were mainly localized in the haloes of insulin granules of beta ( Figure 3 F).…”
Section: Resultssupporting
confidence: 91%
“…The identification of islet cell types, while a simple task by light microscopy and TEM, are much trickier on SEM as there are not many identifying features unequivocally established for endocrine cell groups. We attempted to classify cells by surface morphology, relying on ultrastructural features reported by previous studies of human islets ( 23, 51, 52 ). For example, beta cells are known to express abundant microvilli ( 53, 54 ) which corresponded to a characteristic velvety appearance on their surface ( Figure 2, 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this cannot be done in humans Abbreviations CLSM, confocal laser scanning microscopy; DTA, diphtheria toxin A; ER, endoplasmic reticulum; FP, fluorescent protein; GFP, green fluorescent protein; hpf, hours post-fertilization; MPE, multi-photon excitation; MTZ, metronidazole; NTR, nitroreductase; SPIM, single-plane illumination microscopy; STZ, streptozotocin; T1D, Type 1 diabetes. [8] but various rodent animal models, such as mice and rats [9], have been widely used in T1D research. Yet, visualizing dynamic biological events in vivo in both space and time has remained a complex procedure.…”
Section: Introductionmentioning
confidence: 99%
“…With currently no long‐term alternative treatment to insulin therapy, no cure nor prevention available, fundamental events on the in vivo dynamics of T1D onset and beta cells need to be unravelled. However, this cannot be done in humans [8] but various rodent animal models, such as mice and rats [9], have been widely used in T1D research. Yet, visualizing dynamic biological events in vivo in both space and time has remained a complex procedure.…”
Section: Introductionmentioning
confidence: 99%